2017
DOI: 10.1186/s40199-017-0178-9
|View full text |Cite
|
Sign up to set email alerts
|

Adverse drug reactions and kinetics of cisplatin excretion in urine of patients undergoing cisplatin chemotherapy and radiotherapy for head and neck cancer: a prospective study

Abstract: BackgroundCisplatin is a high-potency anticancer agent; however, it causes significant adverse drug reactions (ADRs). Potential pharmacokinetic markers must be studied to predict or prevent cisplatin-induced ADRs and achieve better prognosis. This study was designed to investigate the relationship between ADRs and kinetics of cisplatin excretion in the urine of patients undergoing high-dose cisplatin chemotherapy and radiotherapy for head and neck cancer.MethodsOutpatients with head and neck cancer received a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0
9

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 33 publications
0
19
0
9
Order By: Relevance
“…Therefore, the effects of RT are potentiated by CDDP 4 . Although the beneficial effects of CDDP are unequivocal, it is associated with numerous side effects involving the hematologic, gastrointestinal, renal, and auditory systems in HNSCC 5,6 . HNSCC patients treated with CDDP may also experience resistance and/or tumour recurrence within five years of follow-up 7 .…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the effects of RT are potentiated by CDDP 4 . Although the beneficial effects of CDDP are unequivocal, it is associated with numerous side effects involving the hematologic, gastrointestinal, renal, and auditory systems in HNSCC 5,6 . HNSCC patients treated with CDDP may also experience resistance and/or tumour recurrence within five years of follow-up 7 .…”
Section: Introductionmentioning
confidence: 99%
“…Erdlenbruch et al 24 demonstrated a correlation between peak urine platinum and the nadir of GFR in 12 children treated with cisplatin. A more recent study by Visacri et al 26 found no association between urine platinum and kidney function after cisplatin infusion. The contradicting results from these studies preclude the ability to draw conclusions regarding the relationship between urine platinum and cisplatin‐associated nephrotoxicity.…”
Section: Discussionmentioning
confidence: 91%
“…Despite the proven e cacy of cisplatin treatment, patients frequently experience toxicity that limits the duration and e cacy of therapy. Nephrotoxicity is one of the most frequent and dose-limiting cisplatininduced toxicities, with a prevalence that varies between 30% and 50% in patients treated with ≥80 mg/m 2 cisplatin [3,4].…”
Section: Read Full License Introductionmentioning
confidence: 99%